2022
DOI: 10.3390/cancers14143380
|View full text |Cite
|
Sign up to set email alerts
|

The Role of CDK Pathway Dysregulation and Its Therapeutic Potential in Soft Tissue Sarcoma

Abstract: Soft tissue sarcomas (STSs) are tumors that are challenging to treat due to their pathologic and molecular heterogeneity and their tumor biology that is not yet fully understood. Recent research indicates that dysregulation of cyclin-dependent kinase (CDK) signaling pathways can be a strong driver of sarcogenesis. CDKs are enzyme forms that play a crucial role in cell-cycle control and transcription. They belong to the protein kinases group and to the serine/threonine kinases subgroup. Recently identified CDK/… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 170 publications
0
3
0
Order By: Relevance
“…One of the most well recognized hallmarks of tumorgenesis is the rapid and uncontrolled growth of cancer cells. The dysregulation of cyclin-dependent kinase (CDK) signaling pathways is thought to be a strong driver of sarcomagenesis [ 8 ]. Cyclin-dependent kinases are serine/threonine kinases that play vital roles in the control and modulation of cell division and transcription in response to various extracellular and intracellular cues.…”
Section: Molecular Mechanisms and Targets For Stsmentioning
confidence: 99%
“…One of the most well recognized hallmarks of tumorgenesis is the rapid and uncontrolled growth of cancer cells. The dysregulation of cyclin-dependent kinase (CDK) signaling pathways is thought to be a strong driver of sarcomagenesis [ 8 ]. Cyclin-dependent kinases are serine/threonine kinases that play vital roles in the control and modulation of cell division and transcription in response to various extracellular and intracellular cues.…”
Section: Molecular Mechanisms and Targets For Stsmentioning
confidence: 99%
“…Cyclin-dependent kinase 2 (CDK-2), a tyrosine kinase, has been shown to exhibit significant regulation of cell cycle progression and transition. It plays crucial roles in gene transcription, phosphorylation of cell cycle proteins, and DNA replication [165]. Numerous studies in the field of scientific research have shown the efficacy of CDK-2 inhibitors in conferring advantageous outcomes in the context of several malignancies, including breast cancer, colorectal cancer, and melanoma [166][167][168].…”
Section: Quinazoline As Egfr/cdk-2 Inhibitorsmentioning
confidence: 99%
“…The comprehensive genomic analysis via The Cancer Genome Atlas (TCGA) has shown that approximately one quarter of all sarcomas harbor genetic alterations in the Cyclin-Dependent Kinase Inhibitor 2A (CDKN2A) - Cyclin D (CCND) - CDK4 - retinoblastoma (RB) axis ( 15 , 16 ), providing strong rationale for targeting this crucial pathway in sarcomas. Hence, better understanding of the role of CDKs in cell biology and cancer, might provide novel avenues of treatment for advanced BSTS ( 14 , 17 ).…”
Section: Introductionmentioning
confidence: 99%